Efficacy of a Newly Modified Short Hydration Method for Gemcitabine and Cisplatin Combination Chemotherapy in Patients with Urothelial Carcinoma - Naiki, Taku (Oncology, 2020)
INTRODUCTION: Conventional first-line chemotherapy for patients with metastatic urothelial carcinoma (UC) is gemcitabine and cisplatin (GC). However, cisplatin can cause renal failure, necessitating abundant fluid replacement and hospitalization during treatment. Recent evidence exists for short hydration methods in cisplatin-based chemotherapy. OBJECTIVE: This study aims to analyze the efficacy of newly established modified short hydration GC (m-shGC) therapy in patients with UC. METHODS: From May 2017 to March 2019, 48 patients with UC who received m-shGC therapy were treated with 1,000 mg/m2 gemcitabine on days 1, 8, and 15, and 70 mg/m2 cisplatin and 2,000 mL fluid replacement on day 1, in each 28-day cycle. We retrospectively evaluated renal function, serum electrolyte abnormalities, and adverse events (AEs) following treatment, and retrospectively compared patients under m-shGC therapy with those under conventional GC (c-GC) therapy from 2015 to 2017. In addition, from April 2019 to August 2019 in a prospective analysis, 15 patients were newly enrolled, and AE profiles and physical activity during m-shGC therapy were quantified using a wearable tracker. RESULTS: In a retrospective analysis of 101 patients (53 c-GC and 48 m-shGC), patient characteristics were not statistically significant between the two groups. Myelosuppression, including predominant neutropenia and decreased platelets, fatigue, nausea, and constipation were the main common AEs. However, renal function and serum sodium levels in the m-shGC group remained unchanged. Grade 3–4 AEs were not more severe in the m-shGC compared with the c-GC group. Furthermore, in a prospective analysis using a wearable tracker, the amount of walking by patients on day 1 significantly declined. However, immediate recovery occurred reflecting the short hydration. CONCLUSION: Our m-shGC therapy has an acceptable AE profile compared with conventional therapy, with UC patients showing good physical activity.